Creating healing spaces for residents using Narrative Medicine - Lijoi, Andre F. (The International Journal of Whole Person Care)

(untitled) (McGill University Library, 2023)
Factors that detract from making meaningful connections with patients and finding meaning and joy in medical practice have found their way into resident education. Burnout and moral injury are increasingly reported by residents across specialties. [1, 2] A curriculum in Narrative Medicine was established at a community hospital family medicine residency as an antidote to these influences. Evaluative survey data and qualitative semi structured interviews reveal that the program created healing spaces for residents. This essay describes the program features and the evidence provided by the residents endorsing the healing impact of the program.